2010
DOI: 10.1038/cdd.2010.73
|View full text |Cite
|
Sign up to set email alerts
|

Trim17, a novel E3 ubiquitin-ligase, initiates neuronal apoptosis

Abstract: Accumulating data indicate that the ubiquitin-proteasome system controls apoptosis by regulating the level and the function of key regulatory proteins. In the present study, we identified Trim17, a member of the TRIM/RBCC protein family, as one of the critical E3 ubiquitin-ligases involved in the control of neuronal apoptosis upstream of mitochondria. We show that expression of Trim17 is increased both at the mRNA and protein level in several in vitro models of transcription-dependent neuronal apoptosis. Expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
76
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(85 citation statements)
references
References 42 publications
8
76
0
Order By: Relevance
“…33,34 We and others have demonstrated that Trim17 is a bona fide E3 ubiquitin-ligase. 25,35 In addition, we have shown that the E3 activity of Trim17 is both necessary and sufficient for the initiation of neuronal apoptosis. 25 Recently, human TRIM17 has been found to stimulate the proteasome-dependent degradation of the kinetochore protein ZWINT.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…33,34 We and others have demonstrated that Trim17 is a bona fide E3 ubiquitin-ligase. 25,35 In addition, we have shown that the E3 activity of Trim17 is both necessary and sufficient for the initiation of neuronal apoptosis. 25 Recently, human TRIM17 has been found to stimulate the proteasome-dependent degradation of the kinetochore protein ZWINT.…”
Section: Discussionmentioning
confidence: 90%
“…25,35 In addition, we have shown that the E3 activity of Trim17 is both necessary and sufficient for the initiation of neuronal apoptosis. 25 Recently, human TRIM17 has been found to stimulate the proteasome-dependent degradation of the kinetochore protein ZWINT. 36 Nevertheless, whether ZWINT is a genuine substrate of TRIM17 has not been demonstrated.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations